Booklet content validation on excess weight for adults with hypertension - Jênifa Cavalcante dos Santos Santiago; Thereza Maria Magalhães Moreira
ABSTRACT Objective: To validate the content and appearance of an educational booklet about excess weight for adults with hypertension. Method: Methodological study in which an educational booklet was developed from theoretical material on hypertension, chronic diseases and obesity, as well as guiding points for the clinical practice of the nurse in the care of young adults with excess weight and based on the Transtheoretical Model. Twenty-one specialists participated in the validation of content and appearance, being 9 teachers, 7 technicians and 5 designers. Results: The Global Content Validity Index was 0.78 and the material was considered appropriate or superior. The experts suggested adjustments, incorporated into the material for print production of the final version. Conclusion: The educational booklet for people with hypertension and excess weight was considered valid regarding content and appearance.